Keterkaitan antara Pengetahuan dan Perilaku Konsumsi terhadap Minuman Fermentasi The Relationship between Knowledge and Consumption Behaviour towards Fermented BeveragesKeterkaitan antara Pengetahuan dan Perilaku Konsumsi terhadap Minuman Fermentasi - Andraeni, Nabila Sukma; Rasmikayati, Elly (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The current lifestyle of the younger generation tends to consume more sweet drinks compared to healthy drinks that have many good benefits for the body. This study aims to determine the relationship between the level of knowledge and consumption behaviour towards fermented drinks in Agribusiness Study Program students. The data analysis tool used is the chi-square test. The results showed that the average respondent had a fairly good knowledge of fermented beverages. Many respondents' consumption behaviour consumed fermented milk beverages because they tasted good with a consumption frequency of less than three times per week. Based on the results of the chi-square test showed a significant relationship (Asym. Sig < 0.1) between gender and knowledge about the types, advantages, disadvantages, and benefits of fermented beverages. Gender variables and diseases that are often experienced are also significantly related to the frequency of consumption of fermented drinks. Then, the pocket money variable has a significant relationship with the price of fermented beverages. In addition, for knowledge of types of fermented beverages with consumption behaviour in the form of frequency showed significant relationship results.